Spinopelvic Alignment in Subjects With Down Syndrome. Issue 6 (July 2018) - Assi, Ayman; Bakouny, Ziad; Mansour, Elie; Yaacoub, Jean-Jacques; Yared, Fares; Ghanem, Ismat
Abstract : Study Design: This was a cross-sectional study. Objective: The aim of this study was to describe the spinopelvic alignment of subjects with Down syndrome (DS). Summary of Background Data: Subjects with DS are known to suffer from a large prevalence of scoliosis. While scoliosis is known to significantly affect postural alignment, there are currently no studies on the spinopelvic alignment of subjects with DS. Materials and Methods: In total, 41 subjects (28 female subjects and 13 male subjects) with DS, age and sex-matched to 41 asymptomatic subjects, underwent biplanar x-rays with 3-dimensional reconstructions of their spines and pelvises, followed by measurement of commonly used spinopelvic sagittal and coronal alignment parameters. Subjects were then classified into one of Roussouly's 4 types of sagittal alignment. Alignment parameters and prevalence of alignment patterns were compared between the 2 groups. Results: Subjects with DS were found to be relatively hypokyphotic (T4–T12=−29.0 vs. −37.5 degrees; P <0.001) and hyperlordotic (L1–L5=53.8 vs. 44.3 degrees; P <0.001) with larger pelvic incidence (53.2 vs. 45.1 degrees; P <0.001), sacral slope (47.7 vs. 36.8 degrees; P <0.001), Cobb angle (10.2 vs. 8.0 degrees; P =0.005), and axial rotation of the apical vertebra (6.6 vs. 3.7 degrees; P <0.001) but had smaller pelvic tilt (4.9 vs. 8.1 degrees; P <0.001) compared with control subjects. Roussouly's type 4 was found to be the most frequent pattern in DS subjects (68.3% vs. 14.6%; P <0.001). Conclusions: Subjects with DS were found to have a peculiar pattern of hypokyphosis, hyperlordosis, large pelvic incidence, and small pelvic tilt. The altered spinopelvic alignment found in DS could predispose these subjects to hip instability and osteoarthritis. Level of Evidence: Level III.